ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN DAERAH AIR MINUM KABUPATEN KUPANG - Marselinda Hege; Kretisana Jagi; Aplonia Atto; Made Susilawati; Dwi Dersmi Selan (Politeknik Negeri Ambon, 2023)
The purpose of this study was to find out and analyze the Financial Performance of Regional Drinking Water Companies in Kupang Regency in terms of financial ratios (liquidity ratios, solvency ratios, activity ratios, profitability ratios) for 2018 – 2020. The data needed in this study are financial reports. The data collection techniques used are documentation and interviews. The data analysis technique used is financial ratio analysis based on the Decree of the Minister of Home Affairs Number 47 of 1999. Financial performance is assessed on a rating ratio scale of 1 (not good) to 5 (very good). The results of this study indicate that the Liquidity Ratio used, namely the current ratio, is included in the classification of very good. Depreciation expense on principal and interest installments is classified as very good. The activity ratio consists of the time period for collection of accounts receivable which is included in the poor classification, the ratio of earning assets to sales is included in the very good classification, the effectiveness ratio for collecting receivables is included in the very good classification. Finally, the Profitability Ratio from 2018 to 2020 has fluctuated. Overall, the financial performance of PDAM Kabupaten Kupang is classified as unfavorable. Implication: To improve financial performance, companies need to increase working capital which has an impact on operating profit. Furthermore, the Company can use productive assets to generate sales